Influence of Peruvian television advertising in unhealthy food consumption in 4th to 6th grade elementary scholars - Rojas-Huayllani, Evelin C. (2013)
Exposure to television advertising promoting unhealthy food consumption may increase overweight and obesity risk in children. Objectives: To determine the influence of Peruvian television advertising and consumption of unhealthy foods in 4th to 6th grade children. Design: Descriptive cross-association. Setting: Educational Institution No. 7072, Villa El Salvador, Lima, Peru. Participants: Schoolchildren aged 9 to 12 years. Interventions: Two previously validated tests were applied to 120 students of both sexes who attended classes and whose parents had signed informed consent. Main outcome measures: Time watching TV and unhealthy food consumption. Results: Students watched TV more than 7 hours per day (DS 1.17) average. Most popular programs were those directed to over 14 year-old public. Most unhealthy foods advertised and purchased were biscuits and sugary drinks. Significant association was found between unhealthy foods most watched by TV and unhealthy food consumption. Conclusions: There was relationship between television advertising and consumption of unhealthy foods in elementary level scholars.